Method for preparing nano cellulose fiber by taking renewable biomass as raw material
Through mechanical and chemical treatment steps, high-purity nanocellulose fibers were successfully extracted from coconut shells and celery rods, solving the environmental pollution and high-temperature and strong acid-base treatment problems of traditional methods, and achieving low-cost and low-pollution nanocellulose Preparation, suitable for the construction of bio-based materials.
Patent Information
- Application Number
- CN202411098236.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively use renewable biomass such as coconut shells and celery rods to prepare nanocellulose fibers, and traditional methods have problems of environmental pollution and high-temperature, strong acid and alkali treatment.
Using mechanical treatment, solvent extraction, bleaching treatment, alkali treatment, washing treatment, TEMPO oxidation and dialysis, nanometers are gradually extracted and purified by heating the water bath of a mixed solution of benzene and ethanol, and the reaction of sodium chlorite and potassium hydroxide. Cellulose fibers avoid high temperature and strong acid and base treatment, and retain the natural structure of cellulose.
It has achieved low-cost and low-pollution extraction of high-purity nanocellulose from coconut shells and celery rods, with high aspect ratio, good dispersion and high crystallinity. It is suitable for building bio-based materials such as nanocellulose aerogels , reducing the energy consumption of subsequent mechanical processing.
Smart Images

Figure CN119265976A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bio-based materials, and in particular to a method for preparing nano cellulose fibers using renewable biomass as raw materials. Background Art
[0002] Cellulose is green, low-cost, easily degradable and renewable, and is gradually becoming a substitute for non-renewable resources represented by petrochemical resources, and is used to prepare advanced functional materials with rich varieties and excellent performance. At present, new bio-based materials such as cellulose balls, cellulose films, cellulose hydrogels and cellulose aerogels have been introduced one after another, and nanocellulose, as an important building block of the above materials, is gaining favor among researchers.
[0003] Nanocellulose refers to cellulose aggregates with a diameter of less than 100nm obtained by processing cellulose bundles from various sources. According to its morphological characteristics, nanocellulose can be divided into cellulose nanocrystals (CNCs), nanocellulose fibers (CNFs) and bacterial cellulose (BCs). Among them, CNFs retain the crystalline and amorphous regions of cellulose, and the length can usually reach several microns. It has the characteristics of high flexibility, easy modification and high aspect ratio, and has broad application prospects in optoelectronics, biomedicine, sensor manufacturing, food packaging and other fields.
[0004] At present, researchers have achieved the extraction of cellulose not only from traditional cellulose sources such as wood pulp, cotton, and bamboo, but also from non-food biomass that are rarely used in industrial cellulose production, such as bagasse, pineapple residue, and cassava residue. The significance of research on non-food bio-based materials is not only to recycle industrial waste from various industrial and agricultural productions and realize "turning waste into treasure", but also to expand the product variety of bio-based materials and obtain renewable materials that meet different actual production needs. In addition, nanocellulose obtained from different cellulose sources often has different physical and chemical properties, which usually affects the functionality of the cellulose-based materials obtained later. Therefore, attempts to prepare nanocellulose from new bio-based materials and analyze their physical and chemical properties are of great guiding significance for the subsequent design of new cellulose-based materials.
[0005] The present invention proposed based on the above factors includes a method for preparing nanocellulose fibers (CNFs) using renewable biomass represented by coconut shells and celery stalks as raw materials, and the method is expected to be expanded to other biomass sources. Coconut is the main oil crop and food energy crop in tropical regions of the world. However, coconut shells are traditionally often used as fuel and fertilizer for recycling, and there is still a lack of means to make them into other forms of products. Using coconut shells as biomass resources to extract nanocellulose can not only enrich the variety of bio-based material products in my country and generate high added value, but also avoid the environmental pollution problems caused by the burning of coconut shells, so it has important research significance. Celery stalks are a common vegetable, and their petioles and stems as edible parts also contain cellulose, and the physical properties of the fibers are quite different from those of cellulose sources such as wood and bacteria. Celery stalks have a large yield, but the current research on their deep-processing products is limited to the food field. Trying to use celery stalks to prepare nanocellulose can not only deepen the understanding of the relationship between the source of cellulose and the physical properties of cellulose materials, but also provide technical reference for extracting cellulose from different types of biomass materials. It can also explore the value of celery stalks as a raw material in the field of materials, increase its added value, and enrich the variety of bio-based material products in my country. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing nanocellulose fibers using renewable biomass as raw materials, wherein the prepared nanocellulose has the characteristics of high aspect ratio, good dispersibility, high crystallinity, and containing carboxylate groups on the surface.
[0007] To achieve the above object, the present invention provides a method for preparing nanocellulose fibers using renewable biomass as raw material, comprising the following steps:
[0008] 1) Mechanical treatment: Renewable biomass is mixed with deionized water and crushed to obtain raw pulp;
[0009] 2) Solvent extraction: using benzene and ethanol to prepare a benzene-alcohol mixed solution and heating it in a water bath, then extracting the slurry obtained in 1), adding deionized water to the slurry after the extraction, removing the residual benzene-alcohol mixed solvent by a rotary evaporator, and then centrifuging to obtain a precipitate;
[0010] 3) Bleaching treatment: prepare a sodium chlorite solution, dissolve the precipitate obtained in 2) in the sodium chlorite solution, add acetic acid and heat in a water bath for reaction, calculate the amount of sodium chlorite in the solution after the reaction is completed, then take the same mass of solid sodium chlorite and acetic acid and add them to the solution for reaction again, and repeat the above steps 2-3 times;
[0011] 4) Alkali treatment: add potassium hydroxide to the solution obtained in 3), stir and centrifuge, take the precipitate and place it in potassium hydroxide solution, heat in a water bath for reaction, and centrifuge to take the precipitate after the reaction is completed;
[0012] 5) Washing treatment:
[0013] If the precipitate obtained in 4) is white, dilute it directly with deionized water and centrifuge to obtain the precipitate;
[0014] If the precipitate obtained in 4) has obvious color, treat the product once according to the process of the initial acid sodium chlorite reaction in 3), repeat 4) after completion, and then dilute with deionized water and centrifuge to obtain the precipitate until the washing liquid is neutral, thereby obtaining a neutral, white cellulose wet pulp;
[0015] 6) TEMPO oxidation: dissolve the white cellulose slurry obtained in 5) with phosphate buffer, then add TEMPO, sodium chlorite and sodium hypochlorite solution, and heat in a water bath for reaction;
[0016] 7) Mechanical treatment: dilute the reaction product obtained in 6) with deionized water and wash it by centrifugation, then perform cell wall breaking treatment on it. After the cell wall breaking treatment, centrifuge and take the supernatant to obtain the nanocellulose fiber solution;
[0017] 8) Subsequent adjustment: The concentration of the nanocellulose solution obtained in 7) is adjusted by a rotary evaporator, and then dialyzed to obtain a purified nanocellulose solution.
[0018] Preferably, in step 1), the renewable biomass is coconut shell or celery stalk.
[0019] Preferably, the usage ratio of renewable biomass to deionized water is 1 g: 2-5 mL, and the mechanical stirring time is 15-30 min.
[0020] Preferably, in step 2), the volume ratio of benzene to ethanol is 2:1, the water bath heating temperature is 90° C.; the extraction treatment time is 6 h; the centrifugal treatment time is 15 min, and the centrifugal speed is 11000 rpm.
[0021] Preferably, in the step 3), the concentration of the prepared sodium chlorite solution is 0.102 mol / L, and the purity of the solid sodium chlorite used is 80%; the acetic acid used is analytically pure, and the amount ratio of the precipitate, the sodium chlorite solution and the acetic acid is 30 g:100 mL:0.769 mL; the water bath heating temperature is 75° C., the water bath heating reaction time is 1 h, and a rotor is added for stirring during the reaction, and the rotor speed is 500 rpm.
[0022] Preferably, in the step 4), the concentration of the potassium hydroxide solution is 5%, the ratio of the precipitate to potassium hydroxide is 30 g:100 mL; the water bath heating temperature is 90° C., the water bath heating reaction time is 2 h, a rotor is added for stirring during the reaction, and the rotor speed is 500 rpm; the centrifugation time is 10 min for both times, and the centrifugation speed is 11000 rpm.
[0023] Preferably, in step 6), the pH of the phosphate buffer is 6.8, the active chlorine content in the sodium hypochlorite solution is 8%-13%; the dosage ratio of cellulose slurry to phosphate buffer is 1g:100mL; the dosage ratio of cellulose slurry to TEMPO is 1g:0.02g; the dosage ratio of cellulose slurry to sodium chlorite is 1g:10mmol; the water bath heating reaction temperature is 60°C, the water bath heating reaction time is 72h, and a rotor is added for stirring during the reaction, and the rotor speed is 600rpm.
[0024] Preferably, in step 7), the centrifugal treatment time is 10 min, the centrifugal speed is 11000 rpm, and the number of centrifugation is 3-5 times; the cell wall breaking treatment time is 10-20 min, the centrifugal treatment time is 20 min, the centrifugal speed is 11000 rpm, and the number of centrifugation is 2-3 times.
[0025] Preferably, in step 8), the concentration of the nanocellulose solution is 0.1%-2%, a 3500Da dialysis bag is used, and the dialysis time is 24 hours.
[0026] Therefore, the present invention provides a method for preparing nanocellulose fibers using coconut shells and celery stalks, two renewable biomasses, as raw materials, and the specific beneficial effects are as follows:
[0027] (1) The present invention uses renewable biomass represented by coconut shells and celery stalks as raw materials to prepare nanocellulose fibers, which has low raw material costs and can also reduce environmental pollution. The preparation method is simple to operate and has a good extraction effect. At the same time, the impurity removal process is detailed and can effectively remove various impurities contained in the raw materials to obtain high-purity cellulose. The obtained nanocellulose can be used to construct other bio-based materials, such as nanocellulose aerogels;
[0028] (2) The extraction process of the present invention is mild and does not require long-term high-temperature cooking and strong acid and alkali treatment. At the same time, cellulose does not need to be dried, so the natural structure of cellulose can be retained as much as possible, which is conducive to the preparation of high-performance nanocellulose and nanocellulose materials;
[0029] (3) The present invention adopts TEMPO-mediated oxidation technology to prepare nanocellulose solution: this technology can selectively oxidize the C6 primary hydroxyl groups on the surface of cellulose chains into carboxyl groups without changing the original crystallinity and crystal morphology of cellulose. The introduction of carboxyl groups helps to increase the electrostatic repulsion between cellulose fibers and greatly reduces the energy consumption of subsequent mechanical treatment. In addition, the reaction conditions of the entire oxidation process are mild, which has great application potential in actual production.
[0030] (4) The nanocellulose product prepared in the present invention is mainly CNFs, which have a diameter of 2-15 nm and a length of 1-5 μm. The obtained nanocellulose solution has obvious birefringence characteristics and high transmittance.
[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The basic flow chart of the invention for extracting nanocellulose fibers from renewable biomass;
[0033] Figure 2 The optical images of samples 1-3 of Example 1 of the present invention, wherein a is sample 1; b is sample 2, and c is sample 3;
[0034] Figure 3 : are microscope images of samples 1-3 of Example 1 of the present invention, wherein a is an optical microscope image of sample 1; b is an optical microscope image of sample 2; c is an atomic force microscope image of sample 3;
[0035] Figure 4 The X-ray diffraction diagrams of sample 1 and sample 3 of Example 1 of the present invention, wherein a is sample 1; b is sample 3;
[0036] Figure 5 The Fourier transform infrared spectra of sample 1 and sample 3 of Example 1 of the present invention are shown in FIG. 1 , wherein a is sample 1; b is sample 3;
[0037] Figure 6 This is an optical image of sample 3 of Example 1 of the present invention under cross polarization;
[0038] Figure 7 This is the UV-visible spectrum of sample 3 of Example 1 of the present invention;
[0039] Figure 8 The optical images of samples 4-6 of Example 2 of the present invention, wherein a is sample 1; b is sample 2, and c is sample 3;
[0040] Fig. 9These are microscope images of samples 4-6 of Example 2 of the present invention, wherein a is an optical microscope image of sample 4; b is an optical microscope image of sample 5; and c is an atomic force microscope image of sample 6;
[0041] Fig.10 The X-ray diffraction patterns of Sample 4 and Sample 6 of Example 2 of the present invention, wherein a is Sample 4; b is Sample 6;
[0042] Fig.11 The Fourier transform infrared spectra of sample 4 and sample 6 of Example 2 of the present invention, wherein a is sample 4; b is sample 6;
[0043] Fig.12 This is an optical image of sample 6 of Example 2 of the present invention under cross polarization;
[0044] Fig.13 This is the UV-visible spectrum of sample 6 in Example 2 of the present invention. DETAILED DESCRIPTION
[0045] The present invention provides a method for preparing nanocellulose fibers using renewable biomass as raw materials. The basic flow chart is as follows: Figure 1 As shown, the following steps are included:
[0046] 1) Mechanical treatment: Renewable biomass is mixed with deionized water and crushed to obtain raw pulp;
[0047] 2) Solvent extraction: using benzene and ethanol to prepare a benzene-alcohol mixed solution and heating it in a water bath, then extracting the slurry obtained in 1), adding deionized water to the slurry after the extraction, removing the residual benzene-alcohol mixed solvent by a rotary evaporator, and then centrifuging to obtain a precipitate;
[0048] 3) Bleaching treatment: prepare a sodium chlorite solution, dissolve the precipitate obtained in 2) in the sodium chlorite solution, add acetic acid and heat in a water bath for reaction, calculate the amount of sodium chlorite in the solution after the reaction is completed, then take the same mass of solid sodium chlorite and acetic acid and add them to the solution for reaction again, and repeat the above steps 2-3 times;
[0049] 4) Alkali treatment: add potassium hydroxide to the solution obtained in 3), stir and centrifuge, take the precipitate and place it in potassium hydroxide solution, heat in a water bath for reaction, and centrifuge to take the precipitate after the reaction is completed;
[0050] 5) Washing treatment:
[0051] If the precipitate obtained in 4) is white, dilute it directly with deionized water and centrifuge to obtain the precipitate;
[0052] If the precipitate obtained in 4) has obvious color, treat the product once according to the process of the initial acid sodium chlorite reaction in 3), repeat 4) after completion, and then dilute with deionized water and centrifuge to obtain the precipitate until the washing liquid is neutral, thereby obtaining a neutral, white cellulose wet pulp;
[0053] 6) TEMPO oxidation: dissolve the white cellulose slurry obtained in 5) with phosphate buffer, then add TEMPO, sodium chlorite and sodium hypochlorite solution, and heat in a water bath for reaction;
[0054] 7) Mechanical treatment: dilute the reaction product obtained in 6) with deionized water and wash it by centrifugation, then perform cell wall breaking treatment on it. After the cell wall breaking treatment, centrifuge and take the supernatant to obtain the nanocellulose fiber solution;
[0055] 8) Subsequent adjustment: The concentration of the nanocellulose solution obtained in 7) is adjusted by a rotary evaporator, and then dialyzed to obtain a purified nanocellulose solution.
[0056] In the present invention, in step 1), the renewable biomass is coconut shell or celery stalk.
[0057] In the present invention, in the step 1), the usage ratio of renewable biomass to deionized water is 1 g: (2-5) mL, and the mechanical stirring time is 15-30 min.
[0058] In the present invention, in the step 2), the volume ratio of benzene to ethanol is 2:1, the water bath heating temperature is 90°C; the extraction treatment time is 6h; the centrifugal treatment time is 15min, and the centrifugal speed is 11000rpm.
[0059] In the present invention, in the step 3), the concentration of the prepared sodium chlorite solution is 0.102 mol / L, and the purity of the solid sodium chlorite used is 80%; the acetic acid used is analytically pure, and the amount ratio of the precipitate, the sodium chlorite solution and the acetic acid is 30 g:100 mL:0.769 mL; the water bath heating temperature is 75° C., the water bath heating reaction time is 1 h, and a rotor is added for stirring during the reaction, and the rotor speed is 500 rpm.
[0060] In the present invention, in the step 4), the concentration of the potassium hydroxide solution is 5%, the ratio of the precipitate to the potassium hydroxide is 30 g:100 mL; the water bath heating temperature is 90° C., the water bath heating reaction time is 2 h, a rotor is added for stirring during the reaction, and the rotor speed is 500 rpm; the centrifugation time is 10 min for both times, and the centrifugation speed is 11000 rpm.
[0061] In the present invention, in the step 6), the pH of the phosphate buffer is 6.8, the active chlorine content in the sodium hypochlorite solution is 8%-13%; the dosage ratio of cellulose slurry to phosphate buffer is 1g:100mL; the dosage ratio of cellulose slurry to TEMPO is 1g:0.02g; the dosage ratio of cellulose slurry to sodium chlorite is 1g:10mmol; the water bath heating reaction temperature is 60°C, the water bath heating reaction time is 72h, and a rotor is added for stirring during the reaction, and the rotor speed is 600rpm.
[0062] In the present invention, in the step 7), the centrifugal treatment time is 10 min, the centrifugal speed is 11000 rpm, and the number of centrifugation is 3-5 times; the cell wall breaking treatment time is 10-20 min, the centrifugal treatment time is 20 min, the centrifugal speed is 11000 rpm, and the number of centrifugation is 2-3 times.
[0063] In the present invention, in step 8), the concentration of the nanocellulose solution is 0.1%-2%, a 3500Da dialysis bag is used, and the dialysis time is 24 hours.
[0064] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without violating the spirit and principle of the present invention should all be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.
[0065] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0066] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0067] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0068] Embodiment 1
[0069] This embodiment provides a method for preparing nanocellulose fibers using coconut shell as raw material, comprising the following steps:
[0070] 1) Weigh 100 g of coconut shell, add 250 mL of deionized water, perform mechanical treatment with a wall breaking machine for 15 min, and filter out excess water with a filter to obtain an initial slurry, which is called sample 1.
[0071] The optical image of sample 1 prepared in this embodiment is as follows: Figure 2 The results show that the appearance of the prepared sample 1 is a brown-yellow, moist flocculent solid.
[0072] Take 1g of sample 1 and dilute it with 10mL of deionized water. Then add a small amount of liquid on a single crystal silicon wafer. After drying at 60℃, the film is characterized by an Olympus BX53M metallographic microscope. The results are as follows: Figure 3 The results show that the initial slurry contains fiber bundles with a length of 200-300 μm, which need to be further dissociated.
[0073] 5 g of sample 1 was placed in a petri dish and dried at 60°C to form a film. The X-ray diffraction experiment was performed using a Bruker D8Advance diffractometer. The results are as follows: Figure 4 The results show that the sample has a peak at 2θ=21.3°, which proves that sample 1 contains cellulose components. At the same time, other characteristic peaks of cellulose do not appear due to the presence of more impurities.
[0074] 5 g of sample 1 was placed in a petri dish and dried into a thin film at 60°C. The Fourier transform infrared spectrum was tested using a Nicolet IS10 spectrometer. The results are as follows: Figure 5 The results show that sample 1 has a peak at 3420 cm-1 corresponding to the hydroxyl group. -1 , 1065cm corresponding to the glycosidic bond -1 The characteristic peaks with strong intensity that are consistent with the chemical structure of cellulose appeared in the sample, indicating the presence of cellulose in the sample. At the same time, due to the impurities in sample 1, several peaks with low intensity that are not related to cellulose can be observed.
[0075] 2) Weigh 100 mL of benzene and 50 mL of ethanol to prepare a benzene-alcohol mixed solution and heat it in a water bath. The water bath temperature is set to 90° C. Take 30 g of sample 1 and extract it for 6 hours. After the extraction is completed, add 50 mL of deionized water to the material, then use a rotary evaporator to remove the residual benzene-alcohol mixed solvent, and centrifuge to obtain a precipitate. The centrifugation time here is 15 minutes, and the centrifugal speed is 11000 rpm.
[0076] 3) Prepare a 0.102 mol / L sodium chlorite solution, take the material obtained after extraction and dissolve it in 100 mL of the above sodium chlorite solution, add 0.769 mL of pure acetic acid and heat it in a water bath at 75°C for 1 hour. After the reaction is completed, weigh 1.154 g of solid sodium chlorite and 0.769 mL of acetic acid and add them to the solution, heat it in a water bath at 75°C for 1 hour again, and repeat twice. All reaction processes are stirred with a rotor at a rotor speed of 500 rpm.
[0077] 4) Add sufficient potassium hydroxide to the solution after the sodium chlorite reaction is completed and stir until the yellow-green color in the solution fades. Then centrifuge the solution to obtain a precipitate. The centrifugation time is 10 minutes and the centrifugal speed is 11000 rpm. Add 100 mL of 5% potassium hydroxide solution to the obtained precipitate, heat in a 90°C water bath for 2 hours, and stir with a rotor at a speed of 500 rpm. After the reaction is completed, centrifuge again to obtain a precipitate, the centrifugation time is 10 minutes, and the centrifugal speed is 11000 rpm.
[0078] 5) The above product was dissolved in 100mL of sodium chlorite solution with a concentration of 0.102mol / L, and 0.769mL of pure acetic acid was added and heated in a water bath at 75°C for 1h. The reaction process was stirred with a rotor at a rotor speed of 500rpm. After the treatment was completed, a sufficient amount of solid potassium hydroxide was added until the color of the solution faded and the solution was centrifuged to obtain a precipitate. The centrifugal treatment time was 10min and the centrifugal speed was 11000rpm. Subsequently, 100mL of deionized water was added repeatedly to dilute the obtained slurry and centrifuged to obtain a precipitate. The centrifugal treatment time was 10min and the centrifugal speed was 11000rpm. The supernatant was treated to be neutral, and excess impurity ions and residual reactants were removed. The precipitate finally obtained in this process was called sample 2. About 1g of sample 2 was taken, its mass was weighed, and it was dried at 60°C. After drying, the mass of the residue was weighed again to determine the water content. The water content of the slurry obtained in this embodiment was 94.22%.
[0079] The optical image of sample 2 prepared in this embodiment is as follows: Figure 2 The results show that the prepared sample 2 is a white, viscous fiber slurry with a high water content.
[0080] Take 1g of sample 2 and dilute it with 10mL of deionized water, then drop a small amount of liquid on a single crystal silicon wafer. After drying at 60℃ to form a film, use an Olympus BX53M metallographic microscope to characterize the morphology. The results are as follows: Figure 3 The results show that after extraction and purification, the fiber chains in the original pulp are initially dissociated into fiber bundles with a length of 200-500 μm.
[0081] 6) 17.3 g of sample 2 was taken to make its dry weight about 1 g, and it was dissolved in 100 mL of phosphate buffer with a pH of 6.8. 0.016 g of TEMPO, 1.13 g of sodium chlorite and 0.7 mL of sodium hypochlorite solution containing 10% active chlorine were added to the above solution, and the mixture was heated in a water bath at 60° C. and stirred at 500 rpm for 72 h.
[0082] 7) The oxidized cellulose solution was centrifuged three times at a speed of 11000 rpm for 10 min each time, and the precipitate was taken. After centrifugation, the solution was diluted with water to 400 mL, placed in a wall breaking machine, and the cellulose solution was treated at a speed of 28000 rpm for 10 min. After the wall breaking machine treatment, the cellulose solution was centrifuged three times for 20 min each time at a speed of 11000 rpm, and the supernatant was taken.
[0083] 8) The concentration was adjusted using a rotary evaporator and the supernatant was dialyzed using a dialysis bag 3500 for 48 hours to obtain a nanocellulose solution with a concentration of 0.25%, which was called sample 3.
[0084] The optical image of sample 2 prepared in this embodiment is as follows: Figure 2 c. The results show that the prepared nanocellulose fiber solution is a uniform, colorless and transparent liquid at a given concentration (0.25%), and the solution is more viscous than the aqueous solution.
[0085] Take 0.1mL sample and drop 3 drops on a single crystal silicon wafer. After drying at 60℃ to form a film, the morphology is characterized by a DimensionalIcon atomic force microscope. The results are as follows: Figure 3 c. The results show that sample 3 contains nanocellulose fibers with a length of 1000-5000 nm and a diameter of 1-10 nm.
[0086] Take 3 drops of 15 mL of the above sample in a petri dish, dry it at 60°C to form a film, and then use a Bruker D8Advance diffractometer to perform an X-ray diffraction experiment. The results are as follows: Figure 4 The results show that after extraction, purification and TEMPO oxidation treatment, there are obvious peaks at 2θ=15.9° and 2θ=21.6°, proving that high-purity and high-crystallinity coconut shell nanocellulose is obtained.
[0087] Take 3 drops of 15 mL sample in a petri dish, dry it into a thin film at 60°C, and use NicoletIS10 spectrometer to test the Fourier transform infrared spectrum. The results are as follows: Figure 5The results show that after extraction and purification, the number and intensity of peaks corresponding to chemical bonds that do not belong to cellulose have decreased. This proves that some impurities in the cellulose pulp have been removed after extraction and purification. -1 The newly appeared peak at corresponds to the carboxyl group, which proves that the TEMPO oxidation process successfully introduced carboxyl groups on the cellulose surface.
[0088] Take 100mL of sample 3 and place it in a glass bottle. Observe the birefringence of the solution. The results are as follows: Figure 6 As shown. The results show that the prepared nanocellulose fiber solution exhibits obvious birefringence. Since the cellulose crystal region belongs to the monoclinic system, it has two optical axes, which makes the nanocellulose fibers dispersed in water show birefringence under light. This proves that the nanocellulose aqueous solution has optical anisotropy and also confirms the presence of nanocellulose fibers in sample 3.
[0089] Take 1 mL of sample 3 and test the UV-visible absorption spectrum using a self-designed spectrometer at room temperature. The results are as follows: Figure 7 The results show that the average transmittance of the solution in the visible light region is 99.06%. According to the light scattering theory, when the particle size of the material is much smaller than the wavelength of light, the Mier scattering effect is weak. According to the AFM characterization results, the particle size of nanocellulose meets the requirement of being much smaller than the wavelength of visible light, which fully proves that nanocellulose has good dispersibility in aqueous solution.
[0090] Embodiment 2
[0091] This embodiment provides a method for preparing nanocellulose fibers using celery stalks as raw materials, comprising the following steps:
[0092] 1) Weigh 100 g of celery stalks, add 250 mL of deionized water, perform mechanical treatment with a wall breaking machine for 15 min, and use a filter to filter out excess water to obtain an initial slurry, which is called sample 4.
[0093] The optical image of sample 4 prepared in this embodiment is as follows: Figure 8 The results show that the appearance of the prepared sample 4 is a light green, moist flocculent solid.
[0094] Take 1g of sample 4 and dilute it with 10mL of deionized water. Then drop a small amount of liquid on a single crystal silicon wafer. After drying at 60℃, use an Olympus BX53M metallographic microscope to characterize the morphology. The results are as follows: Fig. 9 The results show that the initial slurry contains fiber bundles with a length of 200-400 μm, which need to be further dissociated.
[0095] 5 g of sample 4 was placed in a petri dish and dried at 60°C to form a film. The X-ray diffraction experiment was performed using a Bruker D8Advance diffractometer. The results are as follows: Fig.10 The results show that the sample has two characteristic peaks of cellulose at 2θ=16.9° and 2θ=21.7°, but the peak intensity is insufficient due to impurities in the sample.
[0096] 5 g of sample 4 was placed in a petri dish and dried into a thin film at 60°C. The Fourier transform infrared spectroscopy was tested using a Nicolet IS10 spectrometer. The results are as follows: Fig.11 The results show that the infrared spectrum at 3410 cm corresponding to the surface hydroxyl group -1 and 1071cm corresponding to the glycosidic bond -1 The characteristic peaks representing the chemical structure of cellulose appeared at the same time, which confirmed the presence of cellulose in the sample. At the same time, due to the impurities in sample 4, several peaks with lower intensity and unrelated to cellulose can be observed.
[0097] 2) Weigh 100 mL of benzene and 50 mL of ethanol to prepare a benzene-alcohol mixed solution and heat it in a water bath. The water bath temperature is set to 90°C. Take 30 g of sample 4 and extract it for 6 hours. After the extraction is completed, add 50 mL of deionized water to the material, then use a rotary evaporator to remove the residual benzene-alcohol mixed solvent, and centrifuge to obtain a precipitate. The centrifugal treatment time here is 15 minutes, and the centrifugal speed is 11000 rpm.
[0098] 3) Prepare a 0.102 mol / L sodium chlorite solution, take the material obtained after extraction and dissolve it in 100 mL of the above sodium chlorite solution, add 0.769 mL of pure acetic acid and heat it in a water bath at 75°C for 1 hour. After the reaction is completed, weigh 1.154 g of solid sodium chlorite and 0.769 mL of acetic acid and add them to the solution, heat it in a water bath at 75°C for 1 hour again, and repeat twice. All reaction processes are stirred with a rotor at a rotor speed of 500 rpm.
[0099] 4) Add sufficient potassium hydroxide to the solution after the sodium chlorite reaction is completed and stir until the yellow-green color in the solution fades. Then centrifuge the solution to obtain a precipitate. The centrifugation time is 10 minutes and the centrifugal speed is 11000 rpm. Add 100 mL of 5% potassium hydroxide solution to the obtained precipitate, heat in a 90°C water bath for 2 hours, and stir with a rotor at a speed of 500 rpm. After the reaction is completed, centrifuge again to obtain a precipitate, the centrifugation time is 10 minutes, and the centrifugal speed is 11000 rpm.
[0100] 5) The above product was dissolved in 100 mL of sodium chlorite solution with a concentration of 0.102 mol / L, and 0.769 mL of pure acetic acid was added and heated in a water bath at 75°C for 1 hour. The reaction process was stirred with a rotor at a rotor speed of 500 rpm. After the treatment was completed, a sufficient amount of solid potassium hydroxide was added until the color of the solution faded and the solution was centrifuged to obtain a precipitate. The centrifugal treatment time was 10 min and the centrifugal speed was 11000 rpm. Subsequently, 100 mL of deionized water was added repeatedly to dilute the obtained slurry and centrifuged to obtain a precipitate. The centrifugal treatment time was 10 min and the centrifugal speed was 11000 rpm. The supernatant was treated to be neutral, and excess impurity ions and residual reactants were removed. The precipitate finally obtained in this process was called sample 5. About 1 g of sample 5 was taken, its mass was weighed, and it was dried at 60°C. After drying, the mass of the residue was weighed again to determine the water content. The water content of the slurry obtained in this embodiment was 88.2%.
[0101] The optical image of sample 5 prepared in this embodiment is as follows: Figure 8 The results show that the prepared sample 5 is a white, viscous fiber slurry with a high water content.
[0102] Take 1g of sample 5 and dilute it with 10mL of deionized water. Then drop a small amount of liquid on a single crystal silicon wafer. After drying at 60℃, use an Olympus BX53M metallographic microscope to characterize the morphology. The results are as follows: Fig. 9 The results show that after extraction and purification, the fiber chains in the original pulp are initially dissociated into fiber bundles with a length of 200-300 μm.
[0103] 6) 8.48 g of sample 4 was taken to contain about 1 g of slurry, which was dissolved in 100 mL of phosphate buffer with a pH of 6.8. 0.016 g of TEMPO, 1.13 g of sodium chlorite and 0.7 mL of sodium hypochlorite solution containing 10% active chlorine were added to the above solution, and the mixture was heated in a water bath at 60° C. and stirred at 500 rpm for 72 h.
[0104] 7) The oxidized cellulose solution was centrifuged three times at a speed of 11000 rpm for 10 min each time, and the precipitate was taken. After centrifugation, the solution was diluted with water to 400 mL, placed in a wall breaking machine, and the cellulose solution was treated at a speed of 28000 rpm for 10 min. After the wall breaking machine treatment, the cellulose solution was centrifuged three times for 20 min each time at a speed of 11000 rpm, and the supernatant was taken.
[0105] 8) The concentration was adjusted using a rotary evaporator and the supernatant was dialyzed using a dialysis bag 3500 for 48 hours to obtain a nanocellulose solution with a concentration of 0.25%, which was called sample 6.
[0106] The optical image of sample 6 prepared in this embodiment is as follows: Figure 8 c. The results show that the prepared nanocellulose fiber solution is a uniform, colorless and transparent liquid at a given concentration (0.25%), and the solution is more viscous than the aqueous solution, and has similar properties to the nanocellulose fiber solution prepared from coconut shell as raw material.
[0107] Take 0.1mL of sample 6 drops on a single crystal silicon wafer, dry it at 60℃ to form a film, and then use a DimensionalIcon atomic force microscope to characterize the morphology. The results are as follows: Fig. 9 c. The results show that sample 6 contains nanocellulose fibers with a length of 1000-5000 nm and a diameter of 1-5 nm.
[0108] Take 6 drops of 15 mL of the above sample in a petri dish, dry it at 60°C to form a film, and then use a Bruker D8Advance diffractometer to perform an X-ray diffraction experiment. The results are as follows: Fig.10 b. The results show that the X-ray diffraction spectrum has obvious peaks at 2θ=16.3° and 2θ=22.4°, which are close to the characteristic peaks of cellulose, indicating that after extraction, purification and TEMPO oxidation treatment, high-purity and high-crystallinity celery stalk nanocellulose was obtained. However, the test results also show that the crystallinity of the cellulose is lower than that of the coconut shell nanocellulose obtained in Example 1.
[0109] Take 6 drops of 15 mL of the above sample in a petri dish, dry it into a thin film at 60°C, and use NicoletIS10 spectrometer to perform Fourier transform infrared spectroscopy test. The results are as follows: Fig.11 The results show that after extraction and purification, the number and intensity of peaks corresponding to chemical bonds that do not belong to cellulose have decreased. This proves that some impurities in the cellulose pulp have been removed after extraction and purification. -1 A new peak corresponding to the carboxyl group appears at , which proves that the TEMPO oxidation process successfully introduced carboxyl groups on the cellulose surface.
[0110] Take 1 mL of sample 6 and test the UV-visible absorption spectrum using a self-designed spectrometer at room temperature. The results are as follows: Fig.12As shown. The results show that the average transmittance of the solution in the visible light region is 98.04%. According to the light scattering theory, when the particle size of the material is much smaller than the wavelength of light, the Miel scattering effect is weak. According to the AFM characterization results, the particle size of nanocellulose meets the requirement of being much smaller than the wavelength of visible light, which fully proves that nanocellulose has good dispersibility in aqueous solution. At the same time, this result also shows that the nanocellulose solution prepared with celery stalks as raw materials has lower light transmittance than the nanocellulose solution prepared with coconut shells as raw materials. This may be related to the particle size and dispersibility of nanocellulose in the solution, and may affect the physical properties of bio-based materials constructed with it, such as nanocellulose aerogel.
[0111] Take 100mL of sample 6 and place it in a glass bottle. Observe the birefringence of the solution. The results are as follows: Fig.13 As shown. The results show that the prepared nanocellulose fiber solution exhibits obvious birefringence. Since the cellulose crystal region belongs to the monoclinic system, it has two optical axes, which makes the nanocellulose fibers dispersed in water show birefringence under light. This proves that the nanocellulose aqueous solution has optical anisotropy and also confirms the presence of nanocellulose fibers in sample 6.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing nanocellulose fibers using renewable biomass as raw material, characterized in that: The following steps are involved: 1) Mechanical treatment: Renewable biomass is mixed with deionized water and crushed to obtain raw pulp; 2) Solvent extraction: using benzene and ethanol to prepare a benzene-alcohol mixed solution and heating it in a water bath, then extracting the slurry obtained in 1), adding deionized water to the slurry after the extraction, removing the residual benzene-alcohol mixed solvent by a rotary evaporator, and then centrifuging to obtain a precipitate; 3) Bleaching treatment: prepare a sodium chlorite solution, dissolve the precipitate obtained in 2) in the sodium chlorite solution, add acetic acid and heat in a water bath for reaction, calculate the amount of sodium chlorite in the solution after the reaction is completed, then take the same mass of solid sodium chlorite and acetic acid and add them to the solution for reaction again, and repeat the above steps 2-3 times; 4) Alkali treatment: add potassium hydroxide to the solution obtained in 3), stir and centrifuge, take the precipitate and place it in potassium hydroxide solution, heat in a water bath for reaction, and centrifuge to take the precipitate after the reaction is completed; 5) Washing treatment: If the precipitate obtained in 4) is white, dilute it directly with deionized water and centrifuge to obtain the precipitate; If the precipitate obtained in 4) has obvious color, treat the product once according to the process of the initial acid sodium chlorite reaction in 3), repeat 4) after completion, and then dilute with deionized water and centrifuge to obtain the precipitate until the washing liquid is neutral, thereby obtaining a neutral, white cellulose wet pulp; 6) TEMPO oxidation: dissolve the white cellulose slurry obtained in 5) with phosphate buffer, then add TEMPO, sodium chlorite and sodium hypochlorite solution, and heat in a water bath for reaction; 7) Mechanical treatment: dilute the reaction product obtained in 6) with deionized water and wash it by centrifugation, then perform cell wall breaking treatment on it. After the cell wall breaking treatment, centrifuge and take the supernatant to obtain the nanocellulose fiber solution; 8) Subsequent adjustment: The concentration of the nanocellulose solution obtained in 7) is adjusted by a rotary evaporator, and then dialyzed to obtain a purified nanocellulose solution.
2. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 1), the renewable biomass is coconut shell or celery stalk.
3. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: The usage ratio of renewable biomass and deionized water is 1 g: 2-5 mL, and the mechanical stirring time is 15-30 min.
4. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 2), the volume ratio of benzene to ethanol is 2:1, the water bath heating temperature is 90° C.; the extraction treatment time is 6 hours; the centrifugal treatment time is 15 minutes, and the centrifugal speed is 11000 rpm.
5. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 3), the concentration of the prepared sodium chlorite solution is 0.102 mol / L, and the purity of the solid sodium chlorite used is 80%; the acetic acid used is analytical grade, and the amount ratio of the precipitate, the sodium chlorite solution and the acetic acid is 30 g:100 mL:0.769 mL; the water bath heating temperature is 75° C., the water bath heating reaction time is 1 h, and a rotor is added for stirring during the reaction, and the rotor speed is 500 rpm.
6. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 4), the concentration of the potassium hydroxide solution is 5%, and the ratio of the precipitate to potassium hydroxide is 30 g:100 mL; the water bath heating temperature is 90° C., the water bath heating reaction time is 2 h, a rotor is added for stirring during the reaction, and the rotor speed is 500 rpm; the two centrifugation times are both 10 min, and the centrifugal speed is both 11000 rpm.
7. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 6), the pH of the phosphate buffer is 6.8, the active chlorine content in the sodium hypochlorite solution is 8%-13%; the dosage ratio of cellulose slurry to phosphate buffer is 1g:100mL; the dosage ratio of cellulose slurry to TEMPO is 1g:0.02g; the dosage ratio of cellulose slurry to sodium chlorite is 1g:10mmol; the water bath heating reaction temperature is 60°C, the water bath heating reaction time is 72h, and a rotor is added for stirring during the reaction, and the rotor speed is 600rpm.
8. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 7), the centrifugal treatment time is 10 min, the centrifugal speed is 11000 rpm, and the number of centrifugation is 3-5 times; the cell wall breaking treatment time is 10-20 min, the centrifugal treatment time is 20 min, the centrifugal speed is 11000 rpm, and the number of centrifugation is 2-3 times.
9. The method for preparing nanocellulose fibers using renewable biomass as raw materials according to claim 1, characterized in that: In the step 8), the concentration of the nanocellulose solution is 0.1%-2%, a 3500Da dialysis bag is used, and the dialysis time is 24 hours.
Citation Information
Patent Citations
Controllable preparation method of nanocellulose by taking bagasse as raw material
CN114481658A
KR20200028680A